The role of organic nutrients in structuring freshwater phytoplankton communities in a rapidly changing world. (1st July 2022) - Reinl, Kaitlin L.; Harris, Ted D.; Elfferich, Inge; Coker, Ayooluwateso; Zhan, Qing; De Senerpont Domis, Lisette N.; Morales-Williams, Ana M; Bhattacharya, Ruchi; Grossart, Hans-Peter; North, Rebecca L.; Sweetman, Jon N.
Abstract: Carbon, nitrogen, and phosphorus are critical macroelements in freshwater systems. Historically, researchers and managers have focused on inorganic forms, based on the premise that the organic pool was not available for direct uptake by phytoplankton. We now know that phytoplankton can tap the organic nutrient pool through a number of mechanisms including direct uptake, enzymatic hydrolysis, mixotrophy, and through symbiotic relationships with microbial communities. In this review, we explore these mechanisms considering current and projected future anthropogenically-driven changes to freshwater systems. In particular, we focus on how naturally- and anthropogenically- derived organic nutrients can influence phytoplankton community structure. We also synthesize knowledge gaps regarding phytoplankton physiology and the potential challenges of nutrient management in an organically dynamic and anthropogenically modified world. Our review provides a basis for exploring these topics and suggests several avenues for future work on the relation between organic nutrients and eutrophication and their ecological implications in freshwater systems. Graphical abstract: Image, graphical abstract